Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Pegawai Sebagai Variabel Intervening: Studi Kasus Di UPT Puskesmas Babulu - Dendy Bagaskara; Frando Christo Wulur; Ahya Nurdin; Wulan Auliyani; Nurhaeni Sikki (Jurnal Manajemen Riset Inovasi, 2024)
This study aims to examine the effect of competence and work environment on performance mediated by job satisfaction. The approach used in this research is a quantitative approach. The sample used in this study were employees of the Babulu Public Health Center, Penajam Paser Utara Regency, East Kalimantan, totaling 67 employees. The research data was obtained from the results of filling out the questionnaire and analyzed using the SEM PLS analysis technique with the help of the SmartPLS program. The results of this study indicate that competence and work environment have a significant effect on performance either directly or mediated by job satisfaction. High employee competence and supported by a good work environment will increase employee job satisfaction which will further improve their performance.